Caregiver Perception of the Oral-Health-Related Quality of Life of Children with Special Needs: An Exploratory Study - Lidia Gavic; Megi Brekalo; Antonija Tadin (Epidemiologia)
Background: Compared to the general population, individuals with special needs tend to have worse oral health, potentially diminishing their quality of life. This study aimed to evaluate the perception of parents and caregivers regarding the effect of oral health on the quality of life of individuals with special needs who received dental treatment under general anaesthesia, as well as the impact on their and their families’ quality of life. Materials and methods: This cross-sectional study involved participants with special needs who had undergone a dental treatment under general anaesthesia. Before the intervention, an oral examination was conducted to count the number of teeth affected by caries. Parents or caregivers filled out a specially designed questionnaire that included sociodemographic information, details about the children’s oral hygiene and dietary habits, and questionnaires on the impact of their child’s oral health on their quality of life (P-CPQ) and the influence of the oral health of children with psychophysical difficulties on the family (FIS). The data collected were analysed both descriptively and using the chi-square test, Fisher’s exact test, Kruskal–Wallis test, and Spearman’s correlation analysis. The level of significance was set at p ≤ 0.05. Results: This study involved 42 children (24 females and 18 males) with an average age of 21.14 ± 8.34 years. The average number of carious teeth per participant was 9.74 ± 5.63. About 66% of respondents reported that their children performed oral hygiene with their help, while 9.5% of them did not do so at all. Individuals with a higher number of caries had statistically significantly higher scores on the emotional well-being (p = 0.004) and social well-being (p = 0.033) subscales of P-CPQ, as well as on the parental emotions subscale of FIS (p = 0.020). Also, there was a difference in the number of carious teeth in participants due to unhealthy habits (drinking sweetened beverages, p = 0.030) and due to comforting with food (p = 0.004). Conclusion: The increase in the number of carious teeth in individuals with special needs has been associated with the quality of life of their families. To address this, it is crucial to promote the prevention of oral health issues by educating individuals with special needs and their caregivers on proper oral hygiene techniques and diets tailored to their specific requirements.